Prediction of Career Attitudes Based on Future Concern and Perfectionism in University Students - Shiva Mousavi; Seyed AbdolHadi Samavi (Iranian Journal of Educational Research)
Objective: The present study was carried out with the objective of forecasting career attitudes by examining the relationship between future concern and perfectionism among students enrolled at Islamic Azad University of Bandar Lenge. Methods: The research methodology adopted for this study was descriptive in nature, specifically a correlational design. The target population for this study encompassed all students enrolled at Islamic Azad University, Bandar Lenge branch, across different academic levels (i.e., associate, bachelor and master's degrees) in 2024. A stratified random sampling technique was employed to gather data for this research. The instruments utilized for data collection included the career attitude scale (2017) developed by Tarvirdizad et al., Multidimensional Perfectionism Scale (Hoyt & Felt, 1991), and the Dark future scale by Zaleski (2019). To test the research hypotheses, a multiple regression analysis was conducted. Results: The findings from the statistical examination indicated a significant predictive capability of career attitudes by perfectionism and future concern (P<0.05). Conclusions: Consequently, it can be concluded that students at Bandar Lenge University may exhibit positive career attitudes when displaying a noteworthy level of future concern and perfectionism.